2022
DOI: 10.1002/rnc.6037
|View full text |Cite
|
Sign up to set email alerts
|

Constrained fast finite‐time exact tracking for disturbed nonlinear systems

Abstract: This article investigates the fast finite‐time exact tracking problem for nonlinear systems with time‐varying disturbances. A new composite controller with a finite‐time disturbance observer is proposed to achieve fast finite‐time exact tracking. Furthermore, a new time‐varying barrier power integrator technique is developed to design the controller. This can ensure not only asymmetric/symmetric time‐varying full‐state constraints but also singular‐free continuous control effort. To reduce the complexity of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Finite time stabilization means that by designing a proper feedback controller, all the states of the closed loop systems will become exact zero after finite time. [1][2][3][4][5] However, for asymptotic stabilization, the states will converge to zero in an infinite time. Lots of works [6][7][8][9] have shown that finite time control has some promising features in contrast with asymptotic control.…”
Section: Background and Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finite time stabilization means that by designing a proper feedback controller, all the states of the closed loop systems will become exact zero after finite time. [1][2][3][4][5] However, for asymptotic stabilization, the states will converge to zero in an infinite time. Lots of works [6][7][8][9] have shown that finite time control has some promising features in contrast with asymptotic control.…”
Section: Background and Motivationsmentioning
confidence: 99%
“…Finite time stabilization problem has attracted increasing attention in the past few years. Finite time stabilization means that by designing a proper feedback controller, all the states of the closed loop systems will become exact zero after finite time 1‐5 . However, for asymptotic stabilization, the states will converge to zero in an infinite time.…”
Section: Introductionmentioning
confidence: 99%
“…Because finite-time control strategy, which can force the control system to achieve an ideal goal in finite time, has some excellent characteristics such as fast convergence, superior robustness, and disturbance rejection, the research on finite-time stabilization of nonlinear systems has drawn broad and sustained attentions. [1][2][3][4][5][6][7][8][9][10] Numerous works have been conducted on finite-time stability analysis and control strategies. In Reference 2, finite-time stability of continuous but non-Lipschitzian autonomous systems has been investigated and the relationship between regularity properties of Lyapunov function and those of the settling-time function are exposed.…”
Section: Introductionmentioning
confidence: 99%
“…Because finite‐time control strategy, which can force the control system to achieve an ideal goal in finite time, has some excellent characteristics such as fast convergence, superior robustness, and disturbance rejection, the research on finite‐time stabilization of nonlinear systems has drawn broad and sustained attentions 1‐10 . Numerous works have been conducted on finite‐time stability analysis and control strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation